Magnetic Domain Confined Printing of Programmable Organic Microcrystal Assemblies for Information Encryption. Issue 11 (3rd February 2022) - Yin, Baipeng; Jia, Hao; Chen, Rui; Chang, Qingda; Feng, Jiangang; Gao, Hanfei; Wu, Yuchen; Jiang, Lei; Zhang, Chuang
Abstract: Large‐scale assembly of organic micro/nanocrystals into well‐defined patterns with programmable structures is essential for applications such as information encryption at both high data density and high security level. Here, a magnetic‐field‐assisted approach that produces programmable assemblies of organic microcrystals with various shapes and orientations, using the magnetic domains of the underlying ferromagnetic metal microarrays as the printing templates, is developed. The diamagnetic microcrystals tend to aggregate in the regions of minimal field strength, and thus their assembly behavior is precisely controlled by the local field distribution on top of magnetic domains on substrate. The dynamic assembly process of microcrystal assemblies can be programmed upon the sequence of applied field, and their shape changes are ≈100% reproducible on a large scale (>20 000 sites over 1 cm 2 ). These features of magnetically programmable assemblies are ideally suited for information encryption, for which the encryption–decryption–erasing of multilevel information from a QR‐code pattern based on the microcrystal assemblies under magnetic field is demonstrated. Abstract : Programmable organic microcrystal assemblies with dynamic tunable shapes and orientations are manufactured using a virtual, dynamic, noncontact template created by magnetic domain confined printing method. The highly reproducible shape switching enables it to be encoded into a multilevel QR code that encrypts, decrypts, and erases security information by applying a magnetic field.